Situation Report: Bulgaria, 30 October 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reported Defection of Prominent Bulgarian Sculptor Zhivkov's Tour to Southeast Asia Lyudmila Zhivkova's Diplomatic and Cultural Activities in the West Award for Bulgarian Language Studies